"Don't bring me down": Effects of priming secure and anxious attachment on body image. (August 2018) - Homan, Kristin J.; Wild, Samara; Dillon, Kristyn R.; Shimrock, Rachel
Ample evidence has shown that secure attachment is related to more positive body-related attitudes in women. However, existing studies are primarily correlational, leaving questions about causal direction unanswered. This article reports results of two experiments that tested the effects of a guided visualization priming procedure on body image. In Experiment 1, 87 female undergraduates completed a neutral prime at Time 1 and were randomly assigned to either a secure or anxious prime at Time 2. They completed a general measure of body image after each priming task. In Experiment 2, 49 female students and 51 male students completed a neutral prime, a secure prime, and an anxious prime, followed by a measure of body appreciation, at three different sessions 1 week apart. In both studies, women's body image worsened in response to the anxious attachment prime but was unaffected by the secure attachment prime. For women, the effect of the anxious prime was conditional upon body mass index and dispositional attachment anxiety. The primes had no effect on men's body image. Directions for future research, clinical implications, and limitations of the present studies are discussed.